Clinical management of atypical ductal hyperplasia on vacuum-assisted biopsy of microcalcifications: External validation study of a decision tree selecting patients eligible for surveillance. Issue 141 (August 2021) - El Sanharawi, Imane; Bataillon, Guillaume; Journo, Gabrielle; Farkhondeh, Fereshteh; Sebbag-Sfez, Delphine; Malhaire, Caroline; Tardivon, Anne; Mosseri, Véronique; Thibault, Fabienne E.
Highlights: ADH found on percutaneous breast biopsy currently raises management issues. We tested a previously defined decision tree to help obviate unnecessary surgery. Our results support this decision tree with a 5% upgrade in non-operated patients. Abstract: Background: Atypical lesions found on percutaneous breast biopsy raise specific management issues. The aim of this study was to validate the previous performance of a decision tree defined by Forgeard et al to select a subset of patients at low-risk of surgical diagnostic upgrade that would be eligible for surveillance. Methods: A consecutive series of 211 patients diagnosed with ADH on vacuum-assisted biopsy (VAB) of clustered microcalcifications alone, then operated in our institution, was reviewed. Histological findings on percutaneous cores were compared with definitive diagnoses on surgical specimens. The rate of cancer underestimation on VAB was analyzed in the four arms and two management attitudes defined in the scheme, using size and quality of microcalcification removal and the number of ADH foci. Results: Ninety-eight women with ADH met the inclusion criteria. Overall, 20 cancers were diagnosed at surgery, showing a malignancy rate of 44% (17/39 patients) in the surgery group and of 5% (3/59 patients) in the surveillance group, which was not significantly different from the 2% rate in the monitored reference group (p > 0.64). The malignancy rate increased significantly with the size of clustered microcalcifications (0% when < 6mm, 17% when between 6mm and 21 mm, 48% when > 21 mm, p < 0001) and the number of ADH foci on VAB (14% when ≤ 2, 45% when > 2, p < 0.005). Conclusion: Our results corroborate – within the limits of large confidence intervals – those obtained with the reference decision tree. Due to statistical uncertainty, however, they need to be prospectively validated in a broader series.